American Indian biographies - Markowitz, Harvey; Barrett, Carole A. (Salem Press, 2005)
Contains biographical sketches, ranging in length from 300 to 3,000 words, on figures in North American Indian history, extending from the arrival of European colonists on North American shores to the early twenty-first century.
Essays originally appeared in American Indian biographies (1999), Dictionary of world biography, Great lives from history: the Renaissance & early modern era, 1454-1600 (2005), and American ethnic writers (2000). New material has been added.
Keywords: Indians of North America -- Biography.; Indians of North America -- Kings and rulers -- Biography.; Indian women -- North America -- Biography.; Indian authors -- North America -- Biography.; Native peoples -- Biography.; Native peoples -- Kings and rulers -- Biography.; Native women -- North America -- Biography.; Peuples autochtones -- Amérique du Nord -- Biographies.; Peuples autochtones -- Amérique du Nord -- Rois et souverains -- Biographies.; Femmes des Peuples autochtones -- Amérique du Nord -- Biographies.; Écrivains des Peuples autochtones -- Amérique du Nord -- Biographies.; BIOGRAPHY & AUTOBIOGRAPHY -- Historical.; BIOGRAPHY & AUTOBIOGRAPHY -- Native Americans.; Indian authors; Indian women; Indians of North America; Indians of North America -- Kings and rulers; North America; Biographies; Biographies.